Climate emergency – another mayday letter from the EARTH. Issue 2 (3rd April 2021) - Gren, Martin
ABSTRACT: In this letter, addressed to the collective of geographers, the EARTH is begging them to quickly rise up to the unprecedented and urgent challenges that 'the EARTH' and 'them humans' face in this extraordinary grave planetary moment of the climate emergency. With the help of a human ghostwriter, the EARTH accuses geographers for having committed a series of mis-translations, notably by having reduced the EARTH to an extensive 'earth surface' in wait for other agencies like 'Nature', 'Space', 'the Social', 'Culture', 'the Environment', to provide the action. According to the EARTH, this is one of the worst cartographic crimes ever committed in the discipline of geography. Consequently, the EARTH asks geographers to fundamentally reconsider an un-earthly and de-geographized onto-epistemological direction that their discipline generally has taken. Given that the Earth now has evolved into a new kind of geo-being in the Anthropocene, and because the planetary climate emergency means that Terra Oikos is on fire, geographers need to update and revitalize their obsolete geo-ontological conceptual apparatus They must try and save as much, and as fast, as they possibly can, including an EARTH who is in a dire condition and about to leave the Holocene.